Redesain dan Perkuatan Struktur Abutmen Beton Bertulang Jembatan Sumara - Sulendra, I Ketut; Listiawaty, Hilda (JOURNAL TEKNIK SIPIL DAN INFRASTRUKTUR, 2015)
Bridge is one of the most important transportation infrastructures that joining two side of highway thus the bridge is highly needed. To design a bridge geotechnical and hydrological data is crucial as well as characteristic of the river. In the case if a bridge were designed without acurately determine the 50 year return period of flood, then the bridge possiblyÂ  are not save against real flood that may occur. Thus the abutment has to be redesign and retrofitted. Redesign is important to fullfill requirement of high of free space superstructure if the maximum flood occur. Redesign conducted by adding 1,6 m high of the abutment. Controlling stabilities of the abutment i.e: shear and overturning were done. Retrofitting was applied by adding longitudinal and transversal reinforcement with the same dimension and space especially at the joint of transversal reinforcement, transversal reinforcement space reduced to half of its normal space. Longitudinal reinforcement applied was D19-150 and the transversal reinforcement was á´“12-100. To connect the fresh concrete and existing concrete applied material were epoxy resin based produced by PT. SIKA Nusa Pratama SIKADURÂ®732.